2019
DOI: 10.1293/tox.2018-0058
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic features of melanocytic tumors in <i>Xiphophorus</i> melanoma receptor kinase (<i>xmrk</i>)-transgenic medaka (<i>Oryzias latipes</i>)

Abstract: Melanocytic tumors in Xiphophorus melanoma receptor kinase ( xmrk )-transgenic Carbio and HB11A strains of medaka were examined histopathologically at 7 months post-hatching. Medaka of both strains developed melanocytic tumors with a penetrance of 100%. In both strains, neoplastic cells containing intracytoplasmic melanin pigment granules showed significant invasive growth patterns. In addition, epithelioid neoplastic cells were arranged in solid nests, and spindle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…These include a few proto-oncogenes like endothelin receptor ednrbb , sarcoma viral oncogene homolog kita , Ras like estrogen regulated growth factor rerg , pleiotrophin ptn , FYN proto-oncogene fyna , erbb2 receptor tyrosine kinase 3b erbb3b . This evidence, along with previous observation that melanotic tumors are highly invasive into musculature and internal organs while xanthoerythrophoromas grow more as epiphytic nodules [42], suggests the melanoma tumors are more proliferative than xanthoerythrophoromas. Some of these proto-oncogenes are known to be induced by xmrk in Xiphophorus [43-46], culture murine cells, and most of them were reported to be involved in human melanomagenesis [43, 47-52].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These include a few proto-oncogenes like endothelin receptor ednrbb , sarcoma viral oncogene homolog kita , Ras like estrogen regulated growth factor rerg , pleiotrophin ptn , FYN proto-oncogene fyna , erbb2 receptor tyrosine kinase 3b erbb3b . This evidence, along with previous observation that melanotic tumors are highly invasive into musculature and internal organs while xanthoerythrophoromas grow more as epiphytic nodules [42], suggests the melanoma tumors are more proliferative than xanthoerythrophoromas. Some of these proto-oncogenes are known to be induced by xmrk in Xiphophorus [43-46], culture murine cells, and most of them were reported to be involved in human melanomagenesis [43, 47-52].…”
Section: Discussionsupporting
confidence: 75%
“…epiphytic nodules [42], suggests the melanoma tumors are more proliferative than xanthoerythrophoromas. Some of these proto-oncogenes are known to be induced by xmrk in Xiphophorus [43][44][45][46], culture murine cells, and most of them were reported to be involved in human melanomagenesis [43,[47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…These include a few proto‐oncogenes like endothelin receptor ednrbb , sarcoma viral oncogene homolog kita , Ras‐like estrogen‐regulated growth factor rerg , pleiotrophin ptn , FYN proto‐oncogene fyna , and erbb2 receptor tyrosine kinase 3b erbb3b , as well as s1pr3 that is highly expressed in low‐ MITF‐ axis human melanoma. This evidence, along with the previous observation that melanotic tumors are highly invasive into musculature and internal organs while xanthophoromas grow more as epiphytic nodules (Sugiyama et al, 2019), suggests that the melanoma tumors are more proliferative than xanthophoromas. Some of these proto‐oncogenes are known to be induced by xmrk in Xiphophorus (Lu et al, 2015; Schaafhausen et al, 2013; Wellbrock & Schartl, 2000; Wellbrock et al, 2002), culture murine cells, and most of them were reported to be involved in human melanomagenesis (Bittner et al, 2000; Garraway et al, 2005; Gottesdiener et al, 2018; Lu et al, 2015; Natali et al, 1992; Ross et al, 2000; Ryu et al, 2007).…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have revealed that tumor histotypes depend on the genotype of the medaka strain carrying the mitf:xmrk transgene [ 8 , 10 ]. In our experiment Hd-rR displayed formation of either an orange red tumor (xanthoerythrophoroma) or a black tumor (melanoma) or both.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Sugiyama et al. [ 10 ] compared melanocytic tumors occurring in the Carbio and HB11A strains of xmrk -transgenic medaka at 7 months post hatching and confirmed a difference in the pathological features of melanoma formation that was dependent on the genetic background.…”
Section: Introductionmentioning
confidence: 97%